Highly Luminescent Carbon‐Nanoparticle‐Based Materials: Factors Influencing Photoluminescence Quantum Yield. (13th June 2014) - Qu, Songnan; Shen, Dezhen; Liu, Xingyuan; Jing, Pengtao; Zhang, Ligong; Ji, Wenyu; Zhao, Haifeng; Fan, Xiwu; Zhang, Hong
<x xml:space="preserve">Abstract</x> Unravelling the factors influencing photoluminescence (PL) quantum yield of the carbon nanoparticles (CNPs) is the prerequisite for preparing highly luminescent CNP‐based materials. In this work, an easy and effective method is reported for preparing highly luminescent CNP‐based materials. Water‐soluble luminescent CNPs (CNP‐Cs) with large size distribution (1–60 nm) with PL quantum yields of 22% are synthesized through a microwave pyrolysis approach. Energy transfer (ET) is confirmed to occur from small size CNPs (CNP‐Ss:1‐7 nm, blue emitters) to large size CNPs (CNP‐Ls:10–60 nm, green emitters). Further centrifugally separating CNP‐Cs resulted in an enhancement of the PL quantum yield up to 39% of CNP‐Ss aqueous solution. The PL quantum yield of CNP‐Ss could even be further improved in high‐viscosity solvents. PL quantum yield higher than 90% is achieved in films of commercial glue water embedded with the CNP‐Ss at embedding ratio lower than 3 wt%. By contrast, the yield is greatly decreased in the CNP‐C‐embedding films with embedding ratio higher than 1 wt%, which is due to self‐absorption, as well as enhanced ET between CNP‐Ss and CNP‐Ls. High‐viscosity solvents and polymer matrix are proposed to act as surface passivation reagents to enhance PL quantum yield of CNPs.